2015
DOI: 10.1007/s00442-014-3201-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting individual foraging specialization and temporal diet stability across the range of a large “generalist” apex predator

Abstract: Individual niche specialization (INS) is increasingly recognized as an important component of ecological and evolutionary dynamics. However, most studies that have investigated INS have focused on the effects of niche width and inter- and intraspecific competition on INS in small-bodied species for short time periods, with less attention paid to INS in large-bodied reptilian predators and the effects of available prey types on INS. We investigated the prevalence, causes, and consequences of INS in foraging beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 50 publications
5
61
0
Order By: Relevance
“…Recent advances in analytical methods also enable individual-level investigations of diet changes that can provide complementary information to population-level studies, providing insight into individual differences in the speed at which foraging develops in juvenile animals (see Layman et al, 2012 for a review). For example, comparing plasma and red blood cell δ 13 C values, Rosenblatt et al (2015) found that American alligators (Alligator mississippiensis) in the southeastern United States have very stable mixtures of prey taxa in their diets, but individuals can exhibit considerable intraspecific dietary differences, creating individual variation in the topdown effects alligators exert. Further developing methods to quantify individual-level changes in trophic interactions provides a means to test hypotheses generated from population-level studies and gain greater insight at the level of individuals, which is critical for understanding the role phenotypic variability plays in population dynamics and the ecological niches species fill (Bolnick et al, 2011;Sih et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in analytical methods also enable individual-level investigations of diet changes that can provide complementary information to population-level studies, providing insight into individual differences in the speed at which foraging develops in juvenile animals (see Layman et al, 2012 for a review). For example, comparing plasma and red blood cell δ 13 C values, Rosenblatt et al (2015) found that American alligators (Alligator mississippiensis) in the southeastern United States have very stable mixtures of prey taxa in their diets, but individuals can exhibit considerable intraspecific dietary differences, creating individual variation in the topdown effects alligators exert. Further developing methods to quantify individual-level changes in trophic interactions provides a means to test hypotheses generated from population-level studies and gain greater insight at the level of individuals, which is critical for understanding the role phenotypic variability plays in population dynamics and the ecological niches species fill (Bolnick et al, 2011;Sih et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This variability may arise as a result of intrinsic factors such as individual differences in physiology, morphology, or behavior (Killen et al 2011;Patrick and Weimerskirch 2014;Hoskins et al 2015), or from external factors such as prey and habitat availability (Svanbäck and Bolnick 2005;Kernaléguen et al 2015;Newsome et al 2015;Rosenblatt et al 2015). Population-level descriptions largely overlook this individual variability, which may result in incomplete descriptions of foraging behavior and obscure the responses of individuals and populations to environmental variability.…”
Section: Introductionmentioning
confidence: 99%
“…Prey species used in end member calculations were selected based on previous diet studies of coastal alligator populations (Nifong et al, 2015; Nifong et al, 2012; Rosenblatt et al, 2015). The posterior distributions produced by SIAR provide plausible solutions for the proportional contribution of prey sources to the diet of a consumer and incorporates variation in consumer and prey isotope values as well as variation in discrimination factors to provide robust estimates of dietary patterns.…”
Section: Methodsmentioning
confidence: 99%